The Role of The International Community in Establishing Democracy in Myanmar - Adiningtyas Dwiputri Samsoerizal; Eri Radityawara Hidayat; Achmed Sukendro (Universitas Pendidikan Ganesha, 2021)
The existence of differences in Myanmar against the ruling regime is a significant obstacle in building opposition against the military junta. After being generalized in the November 2010 elections, it could be argued that Myanmar has moved away from reclusive authoritarianism but is not yet fully democratized. However, until now, the freedom felt by the people of Myanmar is still limited. It falls under the category of hybrid regimes encountered in the literature as 'not clearly democratic or conventionally authoritarian.' This study aims to analyze the role of the International Community towards Myanmar in promoting democratization. This study describes the political dynamics of Myanmar from its independence until the coup that just occurred in 2021. The method used in this paper is qualitative. This research collects and analyzes data from literature studies and interviews. This study found that international actors who play a role are NGOs, including ASEAN and the US, China, and Indonesia. The military coup has dashed hopes for democracy in Myanmar. The state has committed and reported as a result of civil protests to the military leadership. The coup has influenced the country to decline development in the political, social, and economic fields. In playing democracy, these actors try to develop meaning towards Myanmar using, among others, dialogue between the Myanmar civilians and the military and organizing joint talks. These methods hope Myanmar civilians get the ideal meaning of democracy.